Instruments for measuring self-management and self-care in geriatric patients – a scoping review - Wientzek, Rebecca; Brückner, Rosa Marie; Schönenberg, Aline; Prell, Tino (Frontiers in Public Health, 2023)
Introduction: With demographic changes, prioritizing effective care for geriatric patients to maintain functionality, independence, and quality of life is crucial. Well-developed self-management or self-care abilities, which can be maintained and improved through interventions, are of the utmost importance. To implement these interventions tailored and effectively, a thorough assessment of the individual’s self-management and self-care abilities is required.. Objective: This scoping review aimed to identify self-management and self-care instruments suitable for geriatric patients, their underlying theories and definitions of self-management and self-care, and their similarities and differences in item content. Methods: A systematic search of the PubMed and CINAHL databases was conducted to identify retrievable full-text articles published in English in the medical and nursing fields since the 1970s, which were validated on a sample with an average age of at least 70 years, used generic rather than disease-specific items, and addressed the broad range of self-management and self-care abilities. Results: Of the 20 included articles, six instruments were identified that were based on different theories and offered varying definitions of self-management or self-care. Despite these differences, all emphasize empowered individuals taking an active role in their care. Most address actual behavior and abilities referring to lifestyle factors and (expected) adjustment behavior. However, crucial aspects, such as psychological factors, (instrumental) activities of daily living, and social environment are not fully addressed in these instruments, nor are the types of execution to which the items refer, such as wants, feelings, confidence, or attitudes. Conclusion: To fully understand how geriatric patients implement daily self-management or self-care, a combination of instruments covering the important factors of self-management and self-care and addressing multiple types of item execution, such as behaviors, abilities, wants, or attitudes, is recommended. This review provides the first comprehensive overview of self-management and self-care instruments suitable for geriatric patients.